Observation of the perturbed eigenvalues of PT-symmetric LC resonator systems. (20th April 2021) - Zhou, Bin-Bin; Wang, Li-Feng; Dong, Lei; Huang, Qing-An
Abstract: We address both theoretically and experimentally the influence of asymmetric perturbation on the eigenvalues of parity-time ( PT ) symmetric resonator systems under the symmetric gain-loss arrangement, based on an inductively coupled inductor-capacitor - resistor ( LCR) pair. The perturbed eigenvalues have been theoretically presented, numerically simulated, and experimentally measured. It shows that the asymmetric perturbation breaks PT -symmetry, leading to complex eigenvalues, which is different from the broken PT -symmetric phase with complex-conjugate eigenvalues. We have analyzed the perturbed frequency responses in all phases. At the exceptional points (EP), the resulting eigenvalues splitting is proportional to the square root of perturbation, showing the advantage of being highly sensitive to asymmetric perturbation. Meanwhile, the smaller the perturbation, the higher the sensitivity. The perturbation effect of PT -symmetric systems may be utilized to detect small signal changes in LC passive wireless sensors.